Runoff and sediment yield modeling using GeoWepp in Mapawa Catchment - Puno, George R. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2014)
Determination of runoff and sediment yield in agriculturally active catchment like Mapawa at Lantapan, Bukidnon is important, considering the soil sustainability and productivity. The Geospatial Interface for Water Erosion Prediction Project (GEOWEPP) model was applied and calibrated in this study. The site's average elevation was 1,258 meters above sea level with a slope ranging from 0.5 to 75%. Georeferenced datasets were prepared corresponding to climate, slope, land management, and soil properties. Climate input file was processed from one-year (2002) localized dataset using the breakpoint climate data generator (BPCDG). Slope input file was derived from digital elevation model (DEM). Soil and management input files were derived from field surveys. Separate database files were also created to link WEPP with GIS tool. After series of calibration, runoff and sediment yield were predicted at an average value of 11, 121.0 m3 and 11.2 tons, respectively. The model was validated with Root Mean Square Error (RMSE) (12,153.80), Index of Agreement (IA) (0.55), and the coefficient of determination (R2) value for runoff (0.93). RMSE, IA, and R2 of 5.00, 0.95, and 0.83, respectively, were calculated for sediment yield. Over prediction by the model as evident in larger RMSE values may be attributed to complex varying environmental factors of the catchment that may not be accounted for by the model. Overall, GeoWEPP performed satisfactorily implying applicability in catchment with intensive cultivation and steeper hillslopes.